An Empowerment Toolbox for Older People with Atrial Fibrillation: Results: from the AFFIRMO project: Presenter(s): Serena Barello, Università Cattolica del Sacro Cuore, Italy. (April 2023) - Graffigna, Guendalina; Anderson, Gloria; Bosio, Caterina; De Vita, Maria; Kalra, Dipak; Lane, Deidre; Leo, Donato; Lobban, Trudie C.A.; Ruppe, Georg; Trevisa, Caterina
Abstract : Background: Patient empowerment has been outlined as a specific goal by the World Health Organization's for Europe in Health 2020. In this scenario, Atrial Fibrillation (AF) is a long-term condition where patient empowerment is a fundamental component of successful care. Within this clinical context, the AFFIRMO project, an EU-funded project under the European Union?s Horizon 2020 research and innovation program, is focused on developing and testing the effectiveness of a patient empowerment approach with AF patients with multi-morbidity. Patients are supported by a dedicated ICT platform that empowers them by collecting and using health information. The platform monitors patients' empowerment status to personalize the different empowerment tools provided by the project. This work describes the development of the empowerment toolbox for AFFIRMO project's patients. Methods: Cross-country research was conducted across Europe through the following steps: 1) systematic analysis of the literature to identify "gold-standards" to measure patient empowerment and to identify evidence-based tools for empowering AF patients; 2) empowerment toolbox to improve patients' ability to seek and use health information, with tools customized according to patients' levels of empowerment; and 3) validation interviews with clinicians and patients to optimize the empowerment toolbox. Findings: The literature scan resulted in the identification of 25 validated scales. Only two patient empowerment measures (PHE-S® and PAM®) were identified as adequate tools with consistent psychometric properties. A library of 46 educational materials relevant to patients with AF aimed at increasing their level of empowerment were developed according to the clinical and empowerment profiles of 15 personas. Discussion: The theory-driven toolbox of validated materials is a valuable instrument to orient healthcare professionals in the personalization of AF patient empowerment interventions. Next step is to implement and test the empowerment toolbox with real-world patients enrolled in the AFFIRMO randomised controlled trial via a bespoke electronic platform.